Penolakan Dalam Pelanggaran Prinsip Kerja sama Film Animasi Shalahuddin Al-Ayyubi Episode 6-10 (Kajian Pragmatik) - Sholihat, Isha; Siti Muslikah (Lughaat: Journal of Arabic Linguistics, 2025)
The movie “Saladin Al-Ayyubi” is a movie by Steve Bristow that tells the story of a male Islamic warrior who wants to achieve his goal of becoming a great hero. In the conversation of the movie Saladin Al-Ayyubi episode 6-10, there are a number of violations of the principle of cooperation. These violations give rise to conversational implicatures. The objectives of this research are: 1) To describe the types of violations of the principle of cooperation committed by the characters in the animated film “Saladin Al-Ayyubi” episode 6-10 by Steve Bristow. 2) To describe the conversational implicature that occurs due to the violation of the principle of cooperation in the animated film “Saladin Al-Ayyubi” episode 6-10 by Steve Bristow. The research method used is analytic descriptive method. This method is done by describing and analyzing the data. The method of data collection is by using the listening method followed by note-taking technique. The analysis method used in this research uses the extralingual pairing method. The data source used is taken from the speech of the characters in the movie “Saladin Al-Ayyubi” episode 6-10. The approach uses pragmatic studies. The result of the research revealed is that in the animated movie “Saladin Al-Ayyubi” episode 6-10 there is a violation of the principle of cooperation which includes violation of the maxim of quantity, maxim of quality, maxim of relevance, and maxim of manner or execution. Violation of the principle of cooperation